OCCUPATIONAL SAFETY AS AN IMPORTANT ASPECT FOR DEVELOPMENT OF STEM-EDUCATION IN UKRAINE - Скуйбеда, Елена (Modern engineering and innovative technologies, 2017)
Today education becomes a key aspect of Ukraine's economic development. The main trend in education in the world is the STEM approach (science, technology, engineering, mathematics). Occupational Safety is a discipline that combines engineering, humanitar